KARAKTERISTIK DAN PENANGANAN LIMBAH PADAT SERTA KELUHAN IRITASI KULIT PADA PETUGAS KEBERSIHAN DI PASAR TRADISIONALDAN PASAR MODERN KOTA MEDAN TAHUN 2013 - Sri Isnaini Ritonga; irnawati marsaulina; wirsal hasan (Lingkungan dan Kesehatan Kerja, 2014)
Market is area where the buying and selling of goods with the seller more than onegood something called the shopping centre traditional market, supermarket, shops, mall,plaza, central trade and others.Research is to give in idea of the characteristics and solid waste management marketand complaint skin irritation on janitor in the traditional market and modern market inMedan city 2013.This research is descriptive with sample janitor which totaled 40 people.The characteristic of respondents in the traditional market Penampungan PusatPasar the most common being a janitor ≥ 26 years: 10 people (45,5%), gender is a man: 13people (59,1%), last high school education: 13 people (59,1%), long work ≥ 1 years: 15people (68,2%), working hour ≥ 5 hours: 22 people (100%), ever had complaints of skinirritation: 8 people (36,4%). The characteristic of respondents in the modern marketBerastagi Supermarket, a janitor at most 15-20 years old: 10 people (55,6%), gender is aman: 13 people (55,6%), last high school education: 18 people (100%), long work ≤ 1years: 17 people (94,4%), working hour ≥ 5 hours: 18 people (100%), never hadcomplaints of skin irritation: 18 people (100%). The market Penampungan Central Marketusing traditional Markets do not waste separation while in the modern market madeBerastagi Supermarket waste separation, between the organic and inorganic waste.Advices to departement of market and department of cleansing to providecounseling and socialization regarding waste management which is right and theimportance of the use of a protective self (APD) while working to janitor both in traditionalmarket Penampungan Central Market and modern market Berastagi Supermarket.Keywords: Characteristis, Solid waste, Skin irritation complaint, Janitors, Traditionalmarket and Modern market.